Pengaruh Budaya Organisasi dan Lingkungan Kerja Non Fisik Terhadap Work Life Balance Karyawan pada Generasi Z di Bekasi - Ardila Pratiwi; Eki Prafitri Rahmadani; Ni Made Anjani (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to analyze the influence of organizational culture and non-physical work environment on the work-life balance of Generation Z employees in Bekasi. Generation Z, born between 1997 and 2012, has unique characteristics and special needs that companies need to understand in the world of work. An integrative and collaborative organizational culture and a flexible, adaptable, and non-physical work environment are believed to play an important role in achieving work-life balance. The research method used is quantitative with data collection using a questionnaire of 50 respondents, then processing it using SmartPLS to test validation, reliability, and relationships between variables. The results show that organizational culture significantly affects work life balance, while the non-physical work environment has no significant effect on work life balance.